Bases para la segmentación del mercado homosexual en la ciudad de Lima: un enfoque para el sector de entretenimiento - Regalado Pezúa, Otto (2017)
The homosexual population is an important consumer market for different categories, being the entertainment the most significant. Academic and commercial researchers have addressed this market focusing on developed countries, and considering it a single and homogeneous segment. The following research proposes to set the bases for a segmentation of the homosexual population in Lima, Peru, in order to understand the motives of each identified consumer segment, within the entertainment category. The results allow to identify three segments in the studied population with different demographic, psychographic and behavioral characteristics regarding the consumption of entertainment, which gives rise to different needs and opportunities to satisfy them.